2005
DOI: 10.1124/jpet.105.085597
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Farnesoid-X-Receptor (FXR) and Peroxisome Proliferator-Activated Receptor γ Contributes to the Antifibrotic Activity of FXR Ligands in Rodent Models of Liver Cirrhosis

Abstract: The nuclear receptors farnesoid X receptor (FXR) and peroxisome proliferator-activated receptor (PPAR)␥ exert counterregulatory effects on hepatic stellate cells (HSCs) and protect against liver fibrosis development in rodents. Here, we investigated whether FXR ligands regulate PPAR␥ expression in HSCs and models of liver fibrosis induced in rats by porcine serum and carbon tetrachloride administration and bile duct ligation. Our results demonstrate that HSCs trans-differentiation associated with suppression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(107 citation statements)
references
References 33 publications
3
101
0
Order By: Relevance
“…We found that the expression of fibrotic genes, including PAI-1, type I collagen, fibronectin, and TGF-␤ is increased in human and mouse experimental renal fibrosis models and has been implicated as a major mediator of ECM protein accumulation in diabetic nephropathy and tubulointerstitial fibrosis. [3][4][5][6] Although several nuclear receptors have been reported to regulate TGF-␤ signaling, [27][28][29][30][31] little is known about the clinical significance of nuclear receptors in fibrotic kidney disease. Here we show the role of orphan nuclear receptor SHP in renal fibrosis induced by complete ureteral obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the expression of fibrotic genes, including PAI-1, type I collagen, fibronectin, and TGF-␤ is increased in human and mouse experimental renal fibrosis models and has been implicated as a major mediator of ECM protein accumulation in diabetic nephropathy and tubulointerstitial fibrosis. [3][4][5][6] Although several nuclear receptors have been reported to regulate TGF-␤ signaling, [27][28][29][30][31] little is known about the clinical significance of nuclear receptors in fibrotic kidney disease. Here we show the role of orphan nuclear receptor SHP in renal fibrosis induced by complete ureteral obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, activation of FXR was found to protect from liver 342 ANDERSON AND BORLAK injury in rodent models and was shown to suppress trans-differentiation of stellate cells in vitro (Fiorucci et al, 2004(Fiorucci et al, , 2005a. Likewise, PPAR␥ agonists such as troglitazone and 15-deoxy-⌬ 12,14 -prostaglandin J 2 may have antifibrotic effects in vivo, because they prevented proliferation of human hepatic stellate cell in vitro possibly by a mechanism antagonizing TGF␤1/Smad3-signaling (Marra et al, 2000;Zhao et al, 2006).…”
Section: Novel Targets For Therapeutic Intervention In Nonalcoholimentioning
confidence: 99%
“…The COX-2 inhibitor SC-236 attenuates liver inflammation and fibrosis through PPARγ activation and downregulation of α-SMA expression and MMP-2 and -9 activities, as well as by the induction of Kupffer cells and HSC apoptosis (50). In addition, ligands of the farnesoid X receptor stimulate expression of PPARγ in HSCs and maintain its enhanced levels after injury, thereby promoting the antifibrotic action of PPARγ agonists (51). In addition to their action on HSCs, PPARγ ligands also reduce ductal proliferation and fibrosis after bile duct ligation in rats, showing that PPARγ attenuates fibrosis through not only direct action on matrix-producing cells, but also modulation of the epithelial-mesenchymal interactions in chronic obstructive cholestasis (52).…”
Section: Models Of Intestinal I/r Injury Pparγ Activation Downregulamentioning
confidence: 99%